Phosphatase and Phytase Secreting Efficiency of Some Multipurpose Trees of Arid Region - Yadav, B K; Tarafdar, J C (Annals of Arid Zone, 2016)
Eight tree species were compared for the activity of root associated and root released acid phosphatase and phytase to select the best tree species to exploit native unavailable P for better nutrition. The activity of root associated acid phosphatase and phytase of all genotypes was about 7 to 10 times higher than that of root released acid phosphatase and phytase and the tree species performed differently with regard to the activity of the enzymes. P deficiency increased significantly (P<O.Ol) both acid phosphatase and phytase release. There was a significant correlation (P<O.Ol) between the activities of root associated and root released acid phosphatase and phytase. A significantly higher (P<O.05) phosphatase and phytase activity was observed with the introduction of plants in soil. The results suggested that low phosphorus supply enhanced secretion efficiency of phosphatase and phytase and Acacia nilotica was found to be best tree species to exploit native unavailable phosphorus for their nutrition. Key words: Phosphorus deficiency, acid phosphatase, alkaline phosphatase, phytase. Â